The Nation-State and Global Order A Historical Introduction to Contemporary Politics - Walter C. Opello, Jr. (Lynne Rienner Publishers, 1999)
The seed for this book was planted during a conversation over lunch one day in 1993. During that conversation, the subject of the state came up. Opello, who had been trained as a comparativist and behaviorist in the late 1960s and early 1970s, took the view that the state was little more than a subsystem of the broader social system of which it was a part. He also argued for a hard-and-fast distinction between â€œdomesticâ€ and â€œinternationalâ€ politics, although he recognized that certain â€œissue areasâ€ transcended the boundary of the two. Rosow, who had been trained in political philosophy and international relations in the late 1970s and early 1980s, took a more critical view. He argued that the state was a central construct that had a history. The state, he argued, was an ensemble of relations of power, neither reducible to a social structure nor an autonomous actor. Consequently, Opello began to question his assumptions and began to read the body of literature that had appeared on the state in the 1980s as a critical challenge to mainstream, behavioral political science. That literature, and additional conversations over lunch with Rosow, convinced him that the state should be the central organizing concept of the discipline and should be â€œbrought back in.â€ Once converted to a statist perspective, Opello suggested that he and Rosow develop a course for undergraduates on the history of the state. Opello taught the course, called â€œThe Nation-State and Global Order,â€ for the first time in the spring of 1994. It was then that he realized that the reading available on the state was too advanced for many students. So he suggested to Rosow that they coauthor a textbook written at a level that would make the idea of the state accessible to undergraduates. Rosow agreed, and Opello began to do the research and preliminary writing during the summer of 1994. He finished a draft at the end of the autumn semester 1996. During the academic year 1997, Rosow redrafted the manuscript, moving its conception away from Opelloâ€™s more essentialist perspective. Opello amalgamated the two versions, which were returned to Rosow for additions and correction. The result of this â€œshuttle writingâ€ is the book you have before you. Others have helped make this book possible. At SUNY, Oswego, Karen Nicholas, the History Departmentâ€™s resident classicist and medievalist, read the manuscript and called our attention to a number of historical â€œhowlersâ€ we had made; to her we are deeply grateful. We would like to acknowledge with many thanks the help of Cindy Leflore, the Political Science Department secretary, who good-naturedly typed the first draft of the manuscript from Opelloâ€™s penciled draft. Andy Makal, our international studies assistant, expeditiously checked the accuracy of the many names, dates, and places mentioned in the text as well as the accuracy of the bibliography. Students in the four sections of the â€œNation-State and Global Orderâ€ read and commented on earlier versions of the manuscript. Olivia Opello read the entire manuscript and made numerous helpful suggestions. The comments of the anonymous reviewers helped us tighten the interpretive framework. Opello especially thanks his daughter, Katherine Anne Rose, a graduate student in political science at New York University, who patiently put up with her fatherâ€™s ruminations on the state during their daily runs together when she was home for the holidays. Finally, Rosow thanks Ellen Goldner for her love, support, and friendship over the years of this project, and for graciously putting up with the weekends they could not be together because he remained fixated on a computer screen. None of these people are responsible for any errors in fact or interpretation we have made. Only we carry that responsibility.